Transforming growth factor-beta induces osteoclast formation in the absence of RANKL. - Itonaga, I; Sabokbar, A; Sun, S; Kudo, O; Danks, L; Ferguson, D; Fujikawa, Y; Athanasou, N (2004)
Transforming growth factor beta (TGFbeta) is a multifunctional growth factor that is produced by many cells in bone and is abundant in the bone matrix. TGFbeta is known to regulate RANKL-induced osteoclast formation and bone resorbing activity. In this study we sought to determine whether TGFbeta could directly induce osteoclast formation by a RANKL-independent mechanism. We found that the addition of TGFbeta to cultures of human monocytes and RAW 264.7 cells (in the presence of M-CSF and the absence of RANKL, TNFalpha or IL-6/IL-11) was sufficient to induce the formation of TRAP+ and VNR+ cells, which formed actin rings and were capable of extensive lacunar resorption. The addition of osteoprotegerin or antibodies to TNFalpha and its receptors, as well as antibodies to gp130, did not inhibit lacunar resorption, indicating that TGFbeta did not act by stimulating RANKL, TNF or IL-6 production by monocytes. TGFbeta-induced osteoclast formation was qualitatively different from that induced by RANKL with numerous TRAP+/VNR+ mononuclear and small multinucleated cells being formed; these cells produced many small resorption lacunae. Our results indicate that TGFbeta, which is abundant in the bone matrix, can, in the presence of M-CSF, directly induce mononuclear phagocyte osteoclast precursors to differentiate into osteoclastic cells capable of lacunar resorption.